Importance of transverse plane flexibility for proficiency in golf - McHugh, M. P.; O'Mahoney, C. A.; Orishimo, K. F.; Kremenic, I. J.; Nicholas, S. J. (The Journal of Strength and Conditioning Research, 2022)
The extent to which the flexibility requirements for golf proficiency vary between the planes of motion has not been examined. The purpose of this study was to compare flexibility between proficient and average golfers with the hypothesis that proficient golfers have greater transverse plane flexibility than average golfers, with no differences in the sagittal and frontal planes. Twenty-five male golfers were categorized as proficient (handicap =5, n = 13) or average (handicap 10-20, n = 12). Fourteen flexibility tests were performed (4 shoulder tests, 4 trunk tests, and 6 hip tests) with tests in all 3 planes of motion for each body segment. In addition, trunk motion, pelvic motion, and hip motion during the golf swing were assessed with high-speed motion analysis. Ball speed and shot distance were recorded with a golf simulator. Proficient golfers had significantly better flexibility than average golfers in the transverse plane (shoulder p = 0.021, trunk p = 0.003, and hip p < 0.0001), with no differences in the sagittal plane or frontal plane (plane of motion by golf proficiency p = 0.0001). Transverse plane hip flexibility accounted for 48% of the variability in ball speed (p < 0.0001) and 45% of the variability in total distance (p = 0.001). During the golf swing, proficient golfers had greater separation between the pelvis and the trunk (x-factor) than average golfers (p = 0.002). In conclusion, transverse plane flexibility in the trunk and hips is an important requirement for golf proficiency. Sagittal plane flexibility and frontal plane flexibility were unrelated to proficiency. Developing and maintaining trunk and hip rotation flexibility is important for optimizing performance.